2010
DOI: 10.4088/pcc.09r00895ora
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Bipolar Disorder

Abstract: Adolescence is a vulnerable developmental phase marked by physical, psychological, and social changes that rapidly expose young people to a wide range of new stressors. When differentiating between bipolar disorder and teenage "acting out," a careful history is important. Adolescent bipolar disorder is a psychiatric illness characterized by fluctuating episodes of mood elevation and depression that is frequently neither recognized nor formally diagnosed. Adolescents with bipolar disorder often manifest a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…El trastorno bipolar es una enfermedad mental grave caracterizada por fluctuaciones patológicas del estado de ánimo (episodios de depresión, manía y mixtos) que interfiere en el funcionamiento diario de las personas que lo padecen (1).…”
Section: Introductionunclassified
“…El trastorno bipolar es una enfermedad mental grave caracterizada por fluctuaciones patológicas del estado de ánimo (episodios de depresión, manía y mixtos) que interfiere en el funcionamiento diario de las personas que lo padecen (1).…”
Section: Introductionunclassified
“…However, the presentations of pathological mood changes during adolescence may have particularities that usually complicate their diagnosis [7]. Additionally, it has been demonstrated that the consequences of mood disorders are more severe when they occur before adulthood, with higher rates of chronicity, more comorbidities, and higher risk exposure [8].…”
Section: Diagnosismentioning
confidence: 99%